Insulin signaling in skeletal muscle of HIV‐infected patients in response to endurance and strength training. Issue 3 (22nd August 2013) - Broholm, Christa; Mathur, Neha; Hvid, Thine; Grøndahl, Thomas Sahl; Frøsig, Christian; Pedersen, Bente Klarlund; Lindegaard, Birgitte
Abstract Human immunodeficiency virus (HIV)‐infected patients with lipodystrophy have decreased insulin‐stimulated glucose uptake. Both endurance and resistance training improve insulin‐stimulated glucose uptake in skeletal muscle of HIV‐infected patients, but the mechanisms are unknown. This study aims to identify the molecular pathways involved in the beneficial effects of training on insulin‐stimulated glucose uptake in skeletal muscle of HIV‐infected patients. Eighteen sedentary male HIV‐infected patients underwent a 16 week supervised training intervention, either resistance or strength training. Euglycemic–hyperinsulinemic clamps with muscle biopsies were performed before and after the training interventions. Fifteen age‐ and body mass index (BMI)‐matched HIV‐negative men served as a sedentary baseline group. Phosphorylation and total protein expression of insulin signaling molecules as well as glycogen synthase (GS) activity were analyzed in skeletal muscle biopsies in relation to insulin stimulation before and after training. HIV‐infected patients had reduced basal and insulin‐stimulated GS activity (%fractional velocity, [FV]) as well as impaired insulin‐stimulated Aktthr308 phosphorylation. Despite improving insulin‐stimulated glucose uptake, neither endurance nor strength training changed the phosphorylation status of insulin signaling proteins or affected GS activity. However; endurance training markedly increased the total Akt protein expression, and both training modalities increased hexokinase II (HKII) protein. HIV‐infected patients with lipodystrophy have decreased insulin‐stimulated glucose uptake in skeletal muscle and defects in insulin‐stimulated phosphorylation of Aktthr308. Endurance and strength training increase insulin‐stimulated glucose uptake in these patients, and the muscular training adaptation is associated with improved capacity for phosphorylation of glucose by HKII, rather than changes in markers of insulin signaling to glucose uptake or glycogen synthesis.